OPPORTUNISTIC PRINCIPLE IN THE WORK OF THE OMBUDSMAN - Janković, Saša (Pravni zapisi, 2013)
The paper analyses the normative grounds and justification for the application of the opportunistic principle in the work of the Ombudsman. The Serbian Ombudsman is an independant state authority that protects citizens’ rights by controlling the work of the public authorities and exercising other powers prescribed by statute. The Ombudsman conducts control procedures not only in order to protect the rights of citizens, but also to protect the public interest, which is reflected in the requirement that the public authorities are to work lawfully and correctly and exercise their functions conscientiously and professionaly. The Ombudsman does not decide on citizens’ rights, obligations and interests based on law; the Ombudsman takes informed positions on the work of public authorities and recommends them how to amend possible deficiencies in their work that are detrimental to citizens' rights. The characteristics of the control procedure conducted by the Ombudsman and the very institution of the Ombudsman result in the wide application of the opportunistic principle in his work. This principle was introduced in the control procedure conducted by the Ombudsman indirectly, by an elegant legal technique, which, however, still has its drawbacks.   Key words: Ombudsman, opportunistic principle, the principle of legality, citizens’ complaints.